Reducing Emissions from Fertilizers: Opportunities and Challenges - Khanijo, Bijay Singh; Sapkota, Tek Bahadur (CGIAR System Organization, 2024)
During the last 75 years, production, and consumption of mineral fertilizers, particularly nitrogen ones, contributed enormously to achieve food security but also as much as 5% to global greenhouse gas (GHG) emissions. To meet the Paris Agreement 1.5 °C global warming target, emissions from fertilizer production and use must be effectively curtailed. Potential reduction in the emissions during the production of nitrogen fertilizers can be achieved by using renewable wind and photovoltaic electricity to produce green hydrogen by alkaline water electrolysis, polymer electrolyte membrane water electrolysis, or solid oxide electrolysis cells, which in turn can be used to synthesize green ammonia by the Haber-Bosch process. Combining nitrogen and green hydrogen with a renewable energy-driven N reduction reaction rather than the Haber-Bosch process can further reduce emissions. Nitrous oxide (N2O) is the GHG when N fertilizers are applied to soil. Improving nitrogen use efficiency (NUE) in crop production constitutes the single most effective fertilizer use strategy to reduce N2O emissions. Applying the right amount of fertilizer through the right source and employing the right method of application at the right time of plant demand always improves NUE. If farmers are applying high rates of heavily subsidized fertilizer nitrogen, optimizing the rates has the greatest mitigation potential because it avoids the emissions from both the production and use phase of fertilizers. On-the-go variable rate fertilizer management in large highly mechanized farms in developed countries and site-specific nitrogen management based on low-tech tools in smallholder farms in developing countries leads to reduced N2O emissions by avoiding N application more than the requirement of the crops. Due to high cost and inconsistency in the expected returns of enhanced efficiency fertilizers such as polymer-coated urea and urea stabilized with nitrification and urease, their widespread adoption for mitigating N2O emissions is limited. Integrated management of organic and inorganic nitrogen fertilizers, biochar application, and self-fertilizing crops also have limited usefulness in reducing emissions. Barriers and pathways for sustainable adoption of emission mitigation strategies including support through government policies and motivational change in the attitude of farmers are also discussed.